Dynamic combinatorial mass spectrometry for 2-oxoglutarate oxygenase inhibition - Demetriades, M (2013)
In the last decade, dynamic combinatorial mass spectrometry (DCMS) with protein targets has emerged as a promising method for the identification of enzyme-inhibitors. 2-Oxoglutarate (2OG) oxygenases are involved in important biological processes related to many diseases; several human 2OG oxygenases are targeted for pharmaceutical intervention. This thesis describes inhibition studies on three 2OG oxygenases using DCMS and structure activity relation (SAR) studies. Disulphide based DCMS was used for the identification of N-oxalyl based lead inhibitors for the 2OG oxygenase AlkB from Escherichia coli. Crystallographic analyses of AlkB with a lead inhibitor assisted in the design of a second generation of inhibitors using N-oxalyl, pyridyl and quinolinyl scaffolds. Crystallographic and kinetic data of three potent and selective AlkB inhibitors validates the DCMS approach for the development of 2OG oxygenase inhibitors. The hypoxia inducible factor hydroxylase, prolyl hydroxylase domain 2 (PHD2), was then used as the model enzyme for the development of a novel DCMS approach employing the reversible reaction of boronic acids with diols to form boronate esters. The ‘boronate’ DCMS method was used to identify pyridyl- substituted lead compounds. Further modification of the pyridine scaffold, based on structural analyses, led to the development of highly potent and selective PHD2 inhibitors. To identify inhibitors for the fat mass and obesity associated protein (FTO), another 2OG oxygenase, an inhibition assay was developed. The inhibition assay was used in conjunction with a differential scanning fluorimetry (DSF) binding assay to identify isoquinolinyl and pyridyl inhibitor scaffolds, related to those used in the DCMS studies. FTO complexed structures of these compounds, and with a natural product anthraquinone, enabled the design and synthesis of new inhibitors that are both co-substrate and substrate competitors of FTO. One such compound proved to be a potent FTO inhibitor with improved selectivity over other 2OG oxygenases. Overall, the work validates the use of DCMS methods for the development of potent and selective inhibitors for 2OG oxygenases, and by implication of other enzyme families.